Burden of liver cancer attributable to high fasting plasma glucose: a global analysis based on the global burden of disease study 2019 - Minmin Wang; Jingyi Liu; Liang Yan; Jia Wang; Yinzi Jin; Zhi-Jie Zheng (Elsevier, 2024)
Objective: Liver cancer is the world's sixth most prevalent cancer and the third most frequent cause of cancer-related mortality. Glucose metabolic disorders, indicated by a high fasting plasma glucose (HFPG) concentration, is a contributor to the etiology of liver cancer. With the rising prevalence of glucose metabolic disorders, an assessment of the global burden of liver cancer attributable to HFPG is warranted to inform global liver cancer prevention and control strategies. Methods and analysis: We evaluated the global death and disability-adjusted life years (DALYs) of liver cancer and its subtypes attributable to HFPG at global, regional, and country level. The temporal trend and disparity across geographic regions, social development level, age groups and sex were assessed. Results: In 2019, HFPG-attributable liver cancer was estimated to have caused 4,729.49 deaths and to be responsible for 99,302.25 DALYs. The age-standardized mortality and DALY rate were 0.06 and 1.20 per 100,000 population, and displayed a significantly increasing temporal trend from 1990 to 2019. The age-standardized mortality rate of patients with liver cancer that was attributable to HFPG was higher in men than women. Sex-based disparity narrowed after the women reached menopause, but increased between 1990 and 2019. Conclusion: The burden of liver cancer that are attributable to HFPG has been influenced by longitudinal changes in lifestyle, the etiology of liver disease, age demographics, and hormonal status in women. These findings suggest that comprehensive strategies could be implemented, especially for patients with NASH and hyperglycemia, to prevent liver cancer.